ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING - Muna, Unilatil; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2024)
The automotive industry plays an important role in the Indonesian economy because this industry has a very complete chain, starting from component manufacturing, vehicle production and assembly, network distribution and sales and services to the public, and all of it is capable of absorbing a very large workforce. The aim of this research is to determine the significance of the influence of liquidity, leverage and financial performance on company value through share prices. This research uses descriptive and quantitative research. The population in this study were 11 automotive and component sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique in this research used the Purposive Sampling technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Liquidity has a positive but not significant effect on stock prices, Leverage has a significant negative effect on stock Prices, Financial performance has a significantly positive effect on stock Prices, Liquidity has a negative but not significant effect on company value, Leverage has a negative but not significant effect on company value, financial performance has a negative but not significant effect on company value, share prices have a significant negative effect on company value. The results of the indirect influence hypothesis test show that the variable Liquidity on company value through share prices has a negative but not significant effect, Leverage on company value through share prices has a significant negative effect, Financial performance on company value through share prices has a positive but not significant effect.